2018
DOI: 10.1016/j.imlet.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the T cell response to Chlamydia-sum are better than one

Abstract: Chlamydia trachomatis is responsible for an increasing number of sexually transmitted infections in the United States and is a common cause of serious pathology in the female reproductive tract (FRT). Given the impact and incidence of these infections, the production of an effective Chlamydia vaccine is a public health priority. Mouse models of Chlamydia infection have been utilized to develop a detailed and mechanistic understanding of protective immunity in the FRT. These studies reveal that MHC class-II res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…After infection, naïve CD4 T cells mature into Th1, Th2, Th17, Tfh, or Treg lineages that can help or impede other immune cells to kill microbes. In the case of Chlamydia infection, it is widely believed that CD4 Th1 cells are the major effector lineage that orchestrates bacterial clearance from the reproductive tract [10,11,[21][22][23]. Th1 cells are often required to coordinate the immune response against intracellular pathogens via their capacity to activate macrophages through secretion of IFN-γ [24].…”
Section: Introductionmentioning
confidence: 99%
“…After infection, naïve CD4 T cells mature into Th1, Th2, Th17, Tfh, or Treg lineages that can help or impede other immune cells to kill microbes. In the case of Chlamydia infection, it is widely believed that CD4 Th1 cells are the major effector lineage that orchestrates bacterial clearance from the reproductive tract [10,11,[21][22][23]. Th1 cells are often required to coordinate the immune response against intracellular pathogens via their capacity to activate macrophages through secretion of IFN-γ [24].…”
Section: Introductionmentioning
confidence: 99%
“…For Chlamydia, infection is largely restricted to epithelial cells at barrier tissues such as the eyes, lungs and the reproductive tract. As such, it is reasonable to speculate that protective immunity to Chlamydia would be more complex than Th1-dependent IFN production (9). The mouse models of Chlamydia female reproductive tract infection provide an invaluable tool for studying host immunity to Chlamydia infection.…”
Section: Introductionmentioning
confidence: 99%
“…Chlamydial vaccines have utilized numerous approaches to improve vaccine immunogenicity, including the use of plasmid DNA, recombinant proteins, and subunit antigenic determinants, with or without adjuvants, yet the need for effective preventive measures remains unmet (Brunham and Rey-Ladino, 2005;Vasilevsky et al, 2014). Studies have indicated a critical role for chlamydia-specific CD4 + Th1 T cell responses in the clearing of infection and provision of protective immunity against chlamydia reinfection (Su and Caldwell, 1995;Gondek et al, 2012;Bakshi et al, 2018;Labuda and McSorley, 2018). The chlamydial major outer membrane protein (MOMP) has been shown to induce an immune response comparable to that seen with live bacteria in mice (Pal et al, 2005), while polymorphic membrane proteins (PMPs), have been explored for their ability to induce crossspecies immunogenicity (Pal et al, 2017).…”
Section: Chlamydiamentioning
confidence: 99%